BVT 311/4 – Medical And Urban Entomology [Entomologi Perubatan & Bandar]- January 2014 - PPSKJ, Pusat Pengajian Sains Kajihayat (2014)
First Semester Examination 2013/2014 Academic Session December 2013 / January 2014 Duration: 3 hours